Effects of near-field photon tunneling on the performance of photon–enhanced thermionic emission energy conversion. (January 2019) - Liu, Xianglei; Xia, Haifeng; Xuan, Yimin
Highlights: Performance of photon-enhanced thermionic emission energy conversion is investigated. A theoretical model considering space charge effects and photon tunneling is established. Tradeoff between improved electron emission and thermal radiative losses leads to optimal gap distance. Electron affinity optimization and mismatched thermal radiation further enhance the performance. Abstract: Photon-enhanced thermionic emission (PETE) has been recently proposed as a new concept to achieve full-spectrum solar energy harvesting. Here, we develop a model to consider both space charge effects and near-field photon tunneling losses in evaluating PETE's performance. An optimal gap distance is found to exist, and the underlying mechanism is attributed to soaring thermal radiative losses with decreasing inter-electrode distance beyond the blackbody limit. Further efficiency enhancement approaches are proposed based on electron affinity optimization and mismatched thermal radiation of electrodes. This work helps deepen the understanding of energy transport and conversion processes of PETE devices and guide their optimum designs.